Stress in new graduates: can the profession do more to help?. (18th June 2016) - Halliwell, R. E. W.; Downes, M.; Adams, V. J.; Allister, R.; Harrison, W.; Mellanby, R. J.; Dean, R. S.
Abstract : Richard Halliwell and colleagues believe that it can, on the basis of a survey they conducted to assess the incidence of poor mental health and wellbeing in recent veterinary graduates, and workplace factors that might be associated with this.